The insignificant characters and the grand narrative : a study of multiple implications of the insignificant characters. - Li, Shifang. (2013)
Author Wang An Yi has written numerous excellent pieces of novel. Her two iconic novels “Chang Hen Ge” and “Qi Meng Shi Dai” have received many attentions from scholars and many research papers have written about those two novels. “Chang Hen Ge” is about a life of a woman. However, “Qi Meng Shi Dai” is about a specific year of culture revolution which happened in the China. The two very different themes do not necessary means that they lack of similarity. The latter one can serve as a mirror to reflect on the things have happened in the time period of the former one. Since I am comparing the difference in the narration of history, we have to see it from a different perspective of the History. In this thesis paper, I start from a special angle which is the insignificant characters in these two novels, classify them under different categories. The different categories of insignificant characters can serve as the reflections on the History, and their daily lives also play an importance role in the History. Simultaneously, The thesis base on the theory of “Political Unconsciousness” by Fredric Jameson as one of the arguments to show that those “absence” does not equal to non existence but rather those “absence” are the core information which being hidden. Hence, analyzing insignificant characters does not just restrict to insignificant events, it can be another way round.